Relational Self Psychology. Issue 1 (2nd January 2017) - Magid, Barry; Shane, Estelle
Abstract : Self psychology has evolved beyond Kohut's original one person psychology into a two person intersubjective theory that we propose can now be best understood as belonging to, and developing through interaction with, the broad spectrum of theories that come under the umbrella of Relationality, which are characterized by some form of bi-directionality and mutual influence. Key to this development has been the restoration of the selfobject from psychic function to personhood with its own subjectivity upon which the patient can have and recognize an impact. Kohut's conception of the therapeutic action of the acknowledging and repair of empathic failure can be expanded and enriched by relational ideas of mutual recognition, impact, complementarity, and the Third. Inputs from recent theoretical and experimental developments in the theories of attachment, dynamic systems, and trauma have also contributed to the evolution of what we believe is now a fully Relational Self Psychology.